Ketidaksesuaian perjanjian awal (polis asuransi) dengan hak yang didapat (klaim asuransi) oleh anggota terhadap lembaga asuransi konvensional - Hidayah, Nurul (Maliki Interdisciplinary Journal, 2024)
The initial goal of Insurance Members is generally to build self-protection from all possible losses that may arise in the future. With the establishment of this insurance company, it is hoped that it can fortify these losses. But the fact is that until now, there are still many insurance companies that actually have problems operating, so that many insurance members experience a lot of losses. Reporting from the cnbcindonesia.com page, there are a number of cases in 2022 in cases of embezzlement of members’ policies of up to IDR 12 trillion by PT. Adisarana Wanaartha Life Insurance (Wanaartha Life/PT WAL). In which the Financial Services Authority (OJK) revoked WAL’s business license as a Life Insurance Company because the company was unable to comply with the provisions that were the cause of the imposition of Business Activity Restrictions (PKU) sanctions. And also reported from the Bisnis.com page, in February 2023 OJK handled 4 insurance companies that had problems in their operations, including: Cases of default at PT Asuransi Jiwa Adisarana Wanaartha, Improvement of the Financial Restructuring Plan (RPK) at PT Asuransi Jiwa Kresha, review RPK at Insurance company AJB Bumiputera 1912, and Transfer of Policy portfolio at PT Jiwasraya. Claims that occur in insurance are quite complicated problems. Because it can be seen that the agreement between the company and members cannot be implemented properly. Therefore, a discrepancy arises in the rights that members get when making an initial agreement with the insurance company.